Handbook of climate change and agroecosystems : global and regional aspects and implications - Hillel, Daniel 257359; Rosenzweig, Cynthia 502549 (London : Imperial College Press ; Singapore ; Hackensack, NJ : Distributed by World Scientific Publishing Co., 2011)
Includes bibliographical references and index